Effectiveness of School Interventions in Reducing Bullying Behavior: Systematic Literature Review - Hidayati, Annisa; Marianty, Dewi; Kamila, Aisyah (Utan Kayu Publishing, 2025)
Bullying among adolescents remains a critical issue that affects students' psychological and social well-being. This study analyzes the effectiveness of various school-based interventions in reducing bullying behavior and identifies key factors influencing their success. Utilizing a systematic literature review approach, this study examines research published between 2019 and 2024 from databases such as ScienceDirect, Garuda, and SpringerLink. The Joanna Briggs Institute (JBI) Critical Appraisal checklist and the Mixed Methods Appraisal Tool (MMAT), version 2018, were employed to assess study quality. The findings indicate that school-based interventions are effective when they emphasize relationship-building, empathy, and holistic involvement of all school stakeholders. Consistent program implementation, teacher training, and parental engagement play a crucial role in intervention success. However, challenges such as limited resources, inadequate teacher training, and cultural resistance hinder program effectiveness. Additionally, the study highlights that while interventions improve students' affective empathy, cognitive empathy remains underdeveloped, suggesting the need for more targeted approaches. Practical recommendations include the integration of social-emotional learning in school curricula, teacher professional development programs, and culturally adapted interventions. Policymakers should establish sustainable anti-bullying policies with clear guidelines for intervention and support mechanisms. Future research should explore long-term intervention impacts, digital-based anti-bullying strategies, and the role of genetic and cultural factors in bullying behavior. This study enriches the existing literature by emphasizing the importance of localized, evidence-based intervention strategies tailored to different educational and cultural contexts.